Fetomaternal Outcome in Second Stage Caesarean Section - Khaniya, Bishal (Nepalese Medical Journal, 2020)
Introduction: Second stage caesarean section is usually associated with the deeply engaged head, less liquor, and thinned out the lower uterine segment. This can lead to a high risk of maternal morbidities like an extension of the lower uterine segment incision, uterine atony, and injury to urinary bladder as well as neonatal morbidities such as birth asphyxia, NICU admission, and meconium aspiration syndrome. This study aims to observe the maternal and neonatal outcomes of caesarean delivery performed in the second stage of labor. Materials and Methods: This was a retrospective study of the fetomaternal outcome of all women with singleton, a cephalic fetus at term delivered by caesarean section in the second stage of labor over one year at Tribhuwan University Teaching Hospital. Results: During this study period, there were 4653 deliveries. A total of 2274(48.88%) were born by caesarean section, out of which 1739 (76.5%) were elective and 535(23.5%) were emergency. Among emergency LSCS 36(6.72%) were performed in the second stage of labor. Most of the indications were nondescent of head 34(93.5%) followed by intraoperative maternal complications (hematuria; n=14; 38.88%). Postoperative maternal who had complications were prolong catheterization: 14(38.88%), postoperative fever : 10 (27.77%), prolong hospitalization: 5(13.88%). In perinatal complications meconium stain liquor : 10(27.77%), NNU admissions : 5(13.88%), Apgar score <5 at 5 min : 5 (13.55%), NICU admission : 2(5.54%), fresh stillbirth : 1(2.77%) were observed. Conclusions: Caesarean sections done in the second stage of labor are associated with severe maternal and neonatal complications.